Womenpower: The Presence Of Women In Management, Politics And Academics In Argentina And Worldwide - Kertész, Roberto; Kertész, Victor (European Scientific Journal, ESJ, 2016)
An overview of the present situation and the future trends of women in different management positions is reviewed, including their working profile, educational trends, performance in organizations, entrepreneurship and copreneurship, current national laws ,opportunities in the job place and prospectives, in Argentina and worldwide.